Chaotic Properties of Modified the Kaplan York ‎Map (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
We studied this work investigate the fixed points of modified Kaplan York map k1 and we focus on  found   contracting and expanding area of this map ,Moreover we  study the dynamical system of modified Kaplan York map,is aslo studied  the chaotic properties of k1 proved  the topological entropy of k1 is positive , k1 is sensitive dependence into initial  condition , k1 is transitive finally the Lyapunov exponent is positive .we use mat lab program to show the sensitivity and transitivity of Kaplan York map